2003
DOI: 10.1016/s0168-6445(03)00046-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial mercury resistance from atoms to ecosystems

Abstract: Bacterial resistance to inorganic and organic mercury compounds (HgR) is one of the most widely observed phenotypes in eubacteria. Loci conferring HgR in Gram-positive or Gram-negative bacteria typically have at minimum a mercuric reductase enzyme (MerA) that reduces reactive ionic Hg(II) to volatile, relatively inert, monoatomic Hg(0) vapor and a membrane-bound protein (MerT) for uptake of Hg(II) arranged in an operon under control of MerR, a novel metal-responsive regulator. Many HgR loci encode an additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
917
3
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 915 publications
(956 citation statements)
references
References 281 publications
(546 reference statements)
18
917
3
18
Order By: Relevance
“…This result was different from the previous studies based on short-term incubation experiments showing a negative influence of Hg pollution on the abundance of microorganism Zhou et al 2012). These different effects could be attributed to their different polluted duration by Hg, and some microbial groups in soil might exhibit some resistance or adaptation to long-term Hg stress (Barkay et al 2003). For each site, total abundances of the dsrAB gene in 0-40 cm soil were significantly higher than those in the 40-80 cm soil (P<0.05).…”
Section: Abundance Of Srm In Soilscontrasting
confidence: 99%
“…This result was different from the previous studies based on short-term incubation experiments showing a negative influence of Hg pollution on the abundance of microorganism Zhou et al 2012). These different effects could be attributed to their different polluted duration by Hg, and some microbial groups in soil might exhibit some resistance or adaptation to long-term Hg stress (Barkay et al 2003). For each site, total abundances of the dsrAB gene in 0-40 cm soil were significantly higher than those in the 40-80 cm soil (P<0.05).…”
Section: Abundance Of Srm In Soilscontrasting
confidence: 99%
“…Similar patterns were found in the order of Anaerolineales, envOPS12, SBR1031, and Hydrogenophilales, whose abundances increased with elevated THg and MeHg concentrations. A previous study suggested that the Hg resistance gene (merA), responsible for tolerance to inorganic Hg 2+ , was mainly distributed in Proteobacteria, Actinobacteria and Firmicutes [16], as well as in archeal groups [55]. Nevertheless, our results might imply that the merA gene is more widely distributed in the other microbial groups, because less impact of Hg on these Hgresistant-like bacteria (e.g.…”
Section: Effects Of Hg Contamination On the Distribution Of Bacterialcontrasting
confidence: 60%
“…For example, inorganic Hg 2+ in environments can be reduced to volatile Hg 0 by Hg-resistant bacteria [16]. The resistance of bacteria to inorganic Hg 2+ is associated with the presence of the Hg resistance gene (merA) [16,17], which has been considered widely distributed in the phyla of Firmicutes, Actinobacteria and Proteobacteria [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations